Effects of Parental Sign Language on Academic Achievements of Children with HI in Inclusive Classroom - IFra Sohail, Zaman Ali (JIE, 2023)
This study was aimed to find out the level of parental expertise in sign language and its role for academic achievements of children with HI (HI). The study was descriptive in nature. The participants of this study were 100 children with HI and their hearing parents